2010
DOI: 10.1175/2010jtecha1345.1
|View full text |Cite
|
Sign up to set email alerts
|

A Multisodar Approach to Wind Profiling

Abstract: This paper presents the development of a multisodar mode from a five-beam sodar whereby a wind speed vector is found for sets of three acoustic beams. If the vertical beam is used, this mode enables the profiling of four wind speed measurements around the sodar. These multisodars can be used to investigate the spatial and temporal nature of winds in both flat and complex terrain. The spatial, temporal, and signal-to-noise qualities of the sodar signal in this mode are analyzed, and a metric for understanding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Consequently, we first compared the sodar with mast instrumentation on flat terrain and found a 1% overestimation (see Fig. 4 in Behrens et al 2010). The sodar configuration was identical in the complex terrain, and this ensures that any systematic sodar-related calibration variations will remain the same (at 1%).…”
Section: Potential Flow Resultsmentioning
confidence: 99%
“…Consequently, we first compared the sodar with mast instrumentation on flat terrain and found a 1% overestimation (see Fig. 4 in Behrens et al 2010). The sodar configuration was identical in the complex terrain, and this ensures that any systematic sodar-related calibration variations will remain the same (at 1%).…”
Section: Potential Flow Resultsmentioning
confidence: 99%
“…The various previous studies show the fidelity of the measurement of SODAR systems [9,10] . Behrens Paul et al [11] presented the development of a multisodar from a five-beam SODAR to investigate nature of wind in both complex and flat terrain and validated it against 60 m meteorological mast and found a tight correlation in homogenous terrain with RMS error of 0.4 m/s and R 2 Surface shear stress 0.98. Noord et al [12] reported the SODAR calibration for wind energy application, measurement of power performance of wind turbine using SODAR and operational characteristics.…”
Section: Introductionmentioning
confidence: 99%